The l=2 stellarator with displaced helical windings - Kotenko, V.G.; Romanov, S.S.; Zalkind, V.M. (Вопросы атомной науки и техники, 2007)
The paper deals with the magnetic surface configuration properties in the frame of a new model of the l=2 stellarator with displaced helical windings. The displacement has been made to provide a better access to the plasma confinement volume. Numerical calculations have shown that the magnetic surface configuration, shifted inward the torus and appearing favorable for plasma confinement, can be realized in the absence of a transverse magnetic field.